Conformational changes and fusion activity of influenza virus hemagglutinin of the H2 and H3 subtypes: effects of acid pretreatment. - Puri, A (1990)
Marked differences were observed between the H2 and H3 strains of influenza virus in their sensitivity to pretreatment at low pH. Whereas viral fusion and hemolysis mediated by influenza virus X:31 (H3 subtype) were inactivated by pretreatment of the virus at low pH, influenza virus A/Japan/305/57 (H2 subtype) retained those activities even after a 15-min incubation at pH 5.0 and 37 degrees C. Fusion with erythrocytes was measured by using the octadecylrhodamine-dequenching assay with both intact virions and CV-1 monkey kidney cells expressing hemagglutinin (HA) on the plasma membrane. To study the nature of the differences between the two strains, we examined the effects of low-pH treatment on the conformational change of HA by its susceptibility to protease digestion, exposure of the fusion peptide, and electron microscopy of unstained, frozen, hydrated virus. We found that the respective HA molecules from the two strains assumed different conformational states after exposure to low pH. The relationship between the conformation of HA and its fusogenic activity is discussed in the context of these experiments.